Firm entry and macroeconomic dynamics: A state-level analysis - François Gourio; Todd Messer; Michael Siemer (Federal Reserve Bank of Chicago, 2016)
Using an annual panel of US states over the period 1982-2014, we estimate the response of macroeconomic variables to a shock to the number of new firms (startups). We find that these shocks have significant effects that persist for many years on real GDP, productivity, and population. This is consistent with simple models of firm dynamics where a "missing generation" of firms affects productivity persistently.
Keywords: 330